Islamic Character Education in the Digital Era: A Case Study of Junior High Schools - Ratna Dewi Cahyaningtyas; Aprilia Etika Wardani; M. Makhrus Ali (LP3M Pascasarjana STAI Ibnurusyd, 2025)
This study aims to examine the strategy and implementation of Islamic character education at the Junior High School (SMP) level in facing the challenges of the digital era. Using a qualitative approach through a case study method, this study analyzes the school's efforts to synergize Islamic character values ​​with digital culture that is now part of students' daily lives. The results of the study indicate that the transformation of Islamic character education has been carried out through various strategies, such as the integration of Islamic values ​​in digital media, strengthening Islamic-themed digital literacy, teacher training, and collaboration between schools and parents. However, there are still obstacles such as the gap in teachers' digital competence and unequal access to technology. This study emphasizes the importance of making the digital era an opportunity, not a threat, in forming students' contextual and relevant Islamic character. These findings are expected to provide practical contributions to the development of an integrative and adaptive Islamic character education model.